Літературна творчість Пантелеймона Куліша: ціннісний вимір - Мех, Н. (Культура слова, 2019)
У статті зроблено спробу осмислити аксіологічний вимір
літературної творчості П. Куліша. Висвітлено його філософські
та світоглядні шукання й переконання. Детально розглянуто
резонансний роман «Чорна рада» і його історичне тло.
Проаналізовано твір «Повість про український народ», в якому
відображено послідовну національно-патріотичну позицію,
акцентовано на головних віхах українського минулого. The article attempts to make sense of the axiological dimension of
P. Kulishʼs literary work. His philosophical and philosophical aspirations
and beliefs are covered. His resonant novel Black Council and its historical
background are discussed in detail. In the Ukrainian cultural space, the
period of Ruins has been widely covered. Many Ukrainian artists have
addressed him in their works. Panteleimon Kulish was no exception. He
was very concerned about this topic. He was extremely concerned about
Ukraineʼs future and future. All his multifaceted literary creativity testifies
to this – a powerful stream in the spiritual and national development of the
Ukrainian people.
We also analyze the work of the thinker “Tale of the Ukrainian people”,
in which we see a consistent national-patriotic position, focusing on the
major milestones of our past.
The thinker attached great importance to this work. He was interested
in every review, opinion of his friends, colleagues, contemporaries about
the essay.
Notwithstanding the extralinguistic factors that influenced Р. Kulish,
considering his literary creativity in an axiological dimension, we state the
artist’s heartfelt love for his native Ukraine, for which he made many his
glorious “pen”.
To sum up, we would like to emphasize that the figure of the Ukrainian
thinker, writer, historian Panteleimon Kulish is a significant personality
not only of his age, but also of a figure whose literary creativity influences
the contemporary Ukrainian cultural space, the formation of the values
dominant of the present. His creative and ideological pursuits, his courage,
his ardent patriotism, especially in the early period of his creative work,
his love for his country, his life and history and culture throughout his life,
his longing for freedom are all valuable for generations to come.